Grass Carp Reovirus VP41 Targets Fish MITA To Abrogate the Interferon Response - Lu, Long-Feng (J Virol, 2017)
Although fish possess an efficient interferon (IFN) system to defend against aquatic virus infection, grass carp reovirus (GCRV) still causes hemorrhagic disease in grass carp. To date, GCRV's strategy for evading the fish IFN response is still unknown. Here, we report that GCRV VP41 inhibits fish IFN production by suppressing the phosphorylation of mediator of IFN regulatory factor 3 (IRF3) activation (MITA). First, the activation of the IFN promoter (IFNpro) stimulated by mitochondrial antiviral signaling protein (MAVS) and MITA was decreased by the overexpression of VP41, whereas such activation induced by TANK-binding kinase 1 (TBK1) was not affected. Second, VP41 was colocalized in the cellular endoplasmic reticulum (ER) and associated with MITA. Furthermore, as a phosphorylation substrate of TBK1, VP41 significantly decreased the phosphorylation of MITA. Truncation assays indicated that the transmembrane (TM) region of VP41 was indispensable for the suppression of IFNpro activity. Finally, after infection with GCRV, VP41 blunted the transcription of host IFN and facilitated viral RNA synthesis. Taken together, our findings suggest that GCRV VP41 prevents the fish IFN response by attenuating the phosphorylation of MITA for viral evasion. IMPORTANCE MITA is thought to act as an adaptor protein to facilitate the phosphorylation of IRF3 by TBK1 upon viral infection, and it plays a critical role in innate antiviral responses. Here, we report that GCRV VP41 colocalizes with MITA at the ER and reduces MITA phosphorylation by acting as a decoy substrate of TBK1, thus inhibiting IFN production. These findings reveal GCRV's strategy for evading the host IFN response for the first time.